Determinants of Exclusive Breastfeeding, Early Breastfeeding Cessation, and Recurrent Infections among Stunted Under-Five Children - Dwi Rezeki Auliah; Darmin Darmin; Dea Zara Avila; M.Noris M.Noris (MESINA (Medical Scientific Journal), 2026)
Stunting—characterized by height that is inappropriate for a child's age—is a health issue that poses a long-term threat to a toddler's well-being if left unaddressed. This condition reflects chronic, persistent nutritional deficiency, which has the potential to hinder physical growth, intellectual development, and future productivity. This study aimed to analyze the associations between exclusive breastfeeding, early cessation of breastfeeding, and recurrent infections among stunted toddlers in the working area of the Langgudu Timur Community Health Center (Puskesmas). Methods: A quantitative study was conducted using a case-control design and a retrospective approach involving 90 respondents—mothers of toddlers with either normal nutritional status or stunted status. Sampling was carried out using a combination of probability and purposive sampling. Results: Statistical analysis using the Chi-Square test revealed significant associations between stunting and the variables studied: exclusive breastfeeding (p-value = 0.003 < 0.05; OR = 4.64), early cessation of breastfeeding (p-value = 0.000 < 0.05; OR = 11.00), and recurrent infections (p-value = 0.000 < 0.05; OR = 5.38). It is recommended that all stakeholders strengthen stunting prevention efforts by promoting exclusive breastfeeding for the first six months of life, continuing breastfeeding until the child is two years old or older, and enhancing early prevention and management of infections in toddlers.